Kajian karakteristik spektral daun tanaman tembakau dalam rangka mendukung interpretasi dat penginderaan jauh=Investigation on spectral characteristics of tobacco leaves in the framework of ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT The objective of this research is to study wether the spectral characteristics of tobacco leaves measured with spectrophotometer detector in the laboratory in accordance to that recorded in the landsat TM. Accordingly, spectral characteristics of tobacco leaves of different age were measured with spectrophotometer. Similarly, these characteristics were also acquired from the landsat TM through digital image processing. These two results were then compared. The result of this research indicated that : 1) the absorbtion of tobacco leaves measured with spectrophotmeter characterized healthy tobacco leaves and the stressed ones